A Description of Skeletal Manifestation in Adult Case of Morquio Syndrome: Radiographic and MRI Appearance - Annalisa Di Cesare; Alessandra Di Cagno; Stefano Moffa; Paolucci Teresa; Innocenzi Luca; Arrigo Giombini (Case Reports in Medicine)
We report on a rare case of Morquio syndrome, an autosomal recessive mucopolysaccharidosis including type IVA, a deficiency of N-acetylgalctosamine-6-sulfatase and type IVB a deficiency of β-galactosidase. A 43-year-old female patient affected by IVB Morquio syndrome underwent instrumental investigation. Conventional plain films of the entire spine, pelvis, chest and knees together with magnetic resonance imaging of the entire column, hip, knees, and ankles demonstrated the characteristics of skeletal changes of this disease. The main abnormalities were platyspondily and hypoplasia of the odontoid process, genua valga deformity and severe multiple degenerative changes of the hips, knees, and ankle joints. Radiographs and above all magnetic resonance imaging are crucial to provide substantial information about the gravity, evolution of the skeletal and joints changes, and the rehabilitation strategies to be followed.